DETERMINAN KEBIJAKAN DIVIDEN PADA PERUSAHAAN PUBLIK NON KEUANGAN DI BURSA EFEK INDONESIA - Novita, Dita Ayu; Sukarno, Hari; Puspitasari, Novi (Jurusan Manajemen Fakultas Ekonomi dan Bisnis, 2016)
Abstract: This article aims to analyzethe effects ofthe Investment Opportunity Set, Debt to Equity Ratio, Size, Net Profit Margin, Current Ratio, and Sales Growth on the Dividend Payout Ratio and whether there are differences in each sector of the industry. The data used in this research were secondary data, namely the published financial reports in Indonesia Stock Exchange for the period of 2011 to 2013. A total of 95 companies was used as the samples. Regression Analysis was employed to test the proposed hypothesis. The results showed that the determinants of the dividend policy are Investment Opportunity Set, Debt to Equity Ratio, Size, Net Profit Margin, and Current Ratio. Consumer goods andbasic industry and chemical industry are the industry sectors that can distinguish the Dividend Payout Ratio between these sectors and the other sectors in Indonesia Stock Exchange. Keywords: Dividend Payout Ratio, Regression Analysis, Public Company